PENGUKURAN MATURITY LEVEL COBIT 5 DAN DOMAIN DSS (DELIVER, SERVICE, AND SUPPORT) PADA REGULASI SANDBOX OJK KLASTER AGGREGATOR - Nur Lela sari; Candiwan Candiwan; Helni Mutiarsih Jumhur; Soeparwoto Dharmoputra; Maya Ariyanti (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
With the fast development of the internet and fintech, people have problems in making decisions for choosing the right fintech service or product because currently many of the same services are offered with various applications or web services. Thus, the aggregator cluster Digital Financial Innovation (IKD) service appears at the Financial Services Authority (OJK) to be a solution for users in problems for faster and more precise decision making by conducting site / application comparisons to select the desired service. This research focuses on the aggregator cluster IKD because the fintech sector is the most popular with the community regarding the benefits offered by the sample on services of cermati.com dan lifepal.. The Sandbox regulation is a trial space to assess the reliability of business processes, business models, financial instruments, and governance. organizers, especially in the field of digital financial innovation, including the IKD cluster aggregator. In order for financial products to have a certain status in running their business, they must follow the Sandbox Regulation testing stages so that the OJK as a financial supervisory institution can provide protection for consumers. This study uses qualitative methods with interview data collection techniques. The results of the study were analyzed using Maturity Level COBIT 5 with the DSS (deliver, service, support) selected domain in the sub-domain manage problems and manage business process control for IT management. The results showed that the aggregator cluster based on the selected sample was appropriate in implementing Sandbox Regulation based on 5 stages. The results of the maturity level for the deepening stage are 4.2, the scenario testing stage is 3, the testing and trial stage is 3.3, the improvement stage is 3.2 and the assessment stage is 2.9. The result of maturity level domain manage problem is 3.8 (4), which means that it has entered the predictable level where the process has met the attributes of process measurement and process control, while the domain of manage business process control is 3.3 (3) which means that it has entered an established level where the process has met the process attributes definition and process deployment. Keywords— Regulasi Sandbox, Aggregator, Cluster, Fintech, Maturity Level